THE EFFECT OF EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN MAYBANK BANDAR LAMPUNG - Riyadini Riyan Utami; Zuriana Zuriana; Besty Lilyana; Rizky Ananda Sunandar (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of Emotional Intelligence on Employee Performance, the effect of Organizational Culture on Employee Performance, and the effect of Emotional Intelligence and Organizational Culture on Employee  Performance.   The type of study used quantitative  research using associative method.  The data source used Primary Data.  The data collection method in this study used Field Research techniques with interviews and questionnaires.  The population in this study was 50 employees.  The sample used a purposive sampling technique, namely using the selected criteria totaling 32 employees.  Test the instrument requirements used validity and reliability tests.  Test the data analysis requirements used the normality test, linearity test, and multicollinearity test.   Test data analysis used multiple linear regression analysis.  The results of this study found that Emotional Intelligence had an effect on employee performance. Organizational Culture had an effect on Employee Performance.  Emotional Intelligence and Organizational Culture affeced Performance